Causal relationship between dietary intake and IgA nephropathy: a Mendelian randomization study - Li, Yaping; Wan, Shengli; Liu, Jing; Huang, Yilan; Jiang, Longyang (Frontiers in Nutrition, 2024)
Objective: Previous studies have reported that dietary intake iwas associrelated withto immunoglobulin A nephropathy (IgAN). However,But the causal relationship remains unknown. Based on publicly available genome-wide association study (GWAS) data, we conducted a two-sample Mmendelian randomization (MR) analysis to assess the causal association between 26 dietary exposures and IgAN. Methods: Five methods, including inverse variance weighting (IVW), MR-Egger regression, weighted median, simple mode, and weighted mode, were applied in theour MR analysis. To identify the presence of horizontal pleiotropy, we ustilized the MR-Egger intercept test and MR pleiotropy residual sum and outlier (MR-PRESSO) global test. Cochran's Q statistics were usedemployed to assess the existence of instrument heterogeneity. We conducted a sensitivity analysis using the leave-one-out method. Results: Finally, the results indicated alcohol intake frequency (odds ratio [OR] (95% confidence interval [CI]) =1.242(1.096-1.409) 1.267(1.100-1.460), p = 0.00070.0010295) was a risk factor of IgAN, while cheese intake (OR (95% CI) = 0.626(0.492-0.798)0.669(0.539-0.831), p = 0.00030001559), cereal intake (OR (95% CI) = 0.725(0.527-0.997) 0.652(0.439-0.967), p = 0.04810.0334126), and sushi intake (OR (95% CI) = 0.145(0.021-0.997), p = 0.0497) were protective factors of IgAN. No causal relationship was found between IgAN and the rest of the dietary exposures. Conclusions: Our study provided genetic evidence that alcohol intake frequency was associated with anthe increased risk of IgAN, while cheese intake, cereal, intake and sushi intake were associated with athe decreased risk of IgAN. Further investigations isare requiredneeded to confirm these results.